Magnitude and Determinants of Perinatal Mortality in Southwest Ethiopia - Gurmesa Tura Debelew (Hindawi Limited, 2020)
Despite several efforts globally, the problem of perinatal mortality remained an unsolved agenda. As a result, it continued to be an essential part of the third sustainable development goals to end preventable child deaths by 2030. With a rate of 33 per 1000 births, Ethiopia has the highest level of perinatal mortality in the world. Thus, determining the magnitude and identifying the determinants are very crucial for evidence-based interventions. A community-based longitudinal study was conducted in Southwest Ethiopia among 3474 pregnant women to estimate the magnitude of perinatal mortality. Then, a case-control study among 120 cases and 360 controls was conducted to identify the determinants of perinatal mortality. Data were collected by using an interviewer-administered questionnaire and analyzed by using SPSS version 20. Multivariate logistic regression analysis was used to identify variables having a significant association with perinatal mortality at p<0.05. The perinatal mortality rate was 34.5 (95% CI: 28.9, 41.1) deaths per 1000 births. Attending ≥4 ANC visits (AOR=0.46; 95% CI: 0.23, 0.91), having good knowledge on key danger signs (AOR=0.27; 95% CI: 0.10, 0.75), and having a skilled attendant at birth (AOR=0.34; 95% CI: 0.19, 0.61) were significantly associated with a reduction of perinatal mortality. Being a primipara (AOR=3.38; 95% CI: 1.90, 6.00), twin births (AOR=5.29; 95% CI: 1.46, 19.21), previous history of perinatal mortality (AOR=3.33; 95% CI: 1.27, 8.72), and obstetric complication during labor (AOR=4.27; 95% CI: 2.40, 7.59) significantly increased perinatal mortality. In conclusion, the magnitude of perinatal mortality in the study area was high as compared to the national target for 2020. Care during pregnancy and childbirth and conditions of pregnancy and labor were identified as determinants of perinatal mortality. Hence, interventions need to focus on increasing knowledge of danger signs and utilization of skilled maternity care. Special emphasis needs to be given to mothers with a previous history of perinatal mortality, twin pregnancies, and having obstetric complications.